KEEFEKTIFAN MEDIA PREZI PADA PEMBELAJARAN BUNPOU 2 (PENELITIAN EKSPERIMEN TERHADAP MAHASISWA BAHASA JEPANG TINGKAT I TAHUN AJARAN 2016/2017 FKIP UNIVERSITAS RIAU) - Zulfahriani Z, Mutia; Rahayu, Nana; Isnaini, Zuli Laili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research was to find out the media Prezi effect of the Japanese language (Bunpou 2) on the students level 1 FKIP University of Riau. The research was experimental research which used the type matching only post-test control group design. The object of this research is a Japanese students level 1 riau university consisting of 31 samples one of eksperiment class and control class. Data collection technigue used this research was performed by giving test. The given test was post-test. Post-test is given after the students are taught with media Prezi. This research is processed using statistical tests (T-test) to know whether Ha is accepted or not. Based on statistically analyzing data using the formula it was found that thitung > ttabel (3,32 > 1,67). It means that Ha is accepted and H0 is rejected. The result of this research is that there is a significant impact of using media Prezi of Japanese language (Bunpou 2) on the students level 1 of Japanese Education Department Education Riau University. Level of learning achievement for students in eksperimental class is categorized well (B+) with the average 77,19 and students in control class is categorized sufficient (C) with the average 60,12 . This shows that the use of mediaPrezi on learning Bunpou 2 can improve student achievement.Keywords: Bunpou 2, Media Prezi